IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 14 TAHUN 2011 TENTANG RTRW 2011-2031 MENGENAI PENATAAN RUANG TERBUKA HIJAU DI KECAMATAN MIJEN - Putri, Khansa Adila; Sundarso, Sundarso (Journal of Public Policy and Management Review, 2016)
The arrangement green zone is planning spatial regulation covers semarang city number 14 years.2011 who supported with impetus to maintain its function and managing the green space is.The green space serves as absorbs required in development planning in mijen space.The purpose of this research to find solutions to the green zone private using the regulations no. 14 years 2011 about the spatial semarang city.The result of this research aimed to locate supporters factors and barrier faced by the government to find solutions to the low private green space. This research using the theory the effective implementation of riant nugroho to look at the process implementation and the theory of the van meters and van horn to know factors that encourage and hinder the implementation of policy .This research in a qualitative,using information from bappeda semarang city,the town planning housing,pt.karyadeka nature sustainable and society.This research result indicates that the implementation of the green zone in district mijen started from the design,the use and control.Broad green zone in district mijen until 2015 of 1,15 % to private green space and 49,66 % to public green space of all the area . Factors that encourage and hinder the provision of private green space is size and policy aims,resources,disposition implementor,communication between organization,and economic environment,social and political. Need to be repaired private green space in the form of socialization, establish procedures programs established a systematic,in the effectively and efficient,and using strategy land less by plant in polybag,and other media such as vat, pot cement.